Pengaruh Model Problem Based Learning terhadap Kemampuan berpikir Kritis Mahasiswa Pada Mata Kuliah Filsafat Pendidikan - Desmiarni Desmiarni; Andri Yuliandri; Nizwardi Jalinus (Journal on Education, 2024)
The aim of the research is to determine the effect of the problem based learning model on students' critical thinking abilities in educational philosophy courses. This type of research is meta-analysis research. The data source in the research comes from the analysis of 12 national and international journals published in 2020-2023. The process of searching for data sources through the Google Scholar, ScienceDirect and Researchgate databases. Data search keywords are problem based learning models; critical thinking skills, the influence of the problem based learning model on students' critical thinking skills in philosophy of education courses. The data collection technique is direct observation through journal databases and documentation. Data analysis calculates the effect size value with the help of the JASP application. The results of the research show that there is a significant influence of the problem based learning model on students' critical thinking abilities in educational philosophy courses with an average effect size value (ES = 0.872). These findings provide important information for lecturers to apply the problem based learning model in educational philosophy courses.